Using taxonomic treatments to assess an author’s career: the impactful Jocélia Grazia - Guidoti, Marcus; Simões, Felipe Lorenz; Ruschel, Tatiana Petersen; Da Rosa Gonçalves, Valdenar; Sokolowicz, Carolina; Agosti, Donat (Zootaxa, 2021)
Here we present a descriptive analysis of the bibliographic production of the world-renowned heteropterist Dr. Jocélia Grazia and comments on her taxonomic reach based on extracted taxonomic treatments. We analyzed a total of 219 published documents, including scientific papers, scientific notes, and book chapters. Additionally, we applied the Plazi workflow to extract taxonomic treatments, images, tables, treatment citations and materials citations, and references from 75 different documents in accordance with the FAIR (Findability, Accessibility, Interoperability, and Reuse) principles and made them available on the Biodiversity Literature Repository (BLR), hosted on Zenodo, and on TreatmentBank. We found that Dr. Grazia published 200 new names, including species (183) and genera (17), and 1,444 taxonomic treatments in total. From these, 104 and 581, respectively, were extracted after applying the Plazi Workflow. A total of 544 figures, 50 tables, 2,242 references, 2,107 materials citations, and 1,101 treatment citations were also extracted. In order to make her publications properly citable and accessible, we assigned DOIs (Digital Object Identifiers) for all publications that lacked this persistent identifier, including those that were not processed (88 in total), therefore enhancing the open-access share of her publications.